2022
DOI: 10.5829/ije.2022.35.09c.14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tensile Load on Bonding Strength of Asphalt Concrete Containing Modified Buton Asphalt and Polyethylene Terephthalate Waste: A Case Study of Indonesian Roads

Abstract: Development of transportation networks supported by rigid pavement, flexural pavement, and others paved road provides efficient movement of people between different areas and improves supply chain and goods distribution. In addition, an increase in vehicle volume is accompanied by the increase in vehicle axle loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The Toughness Index (TI) is a parameter that describes the characteristics of toughness, which, as determined by the stress-strain curve, is the mixture's capacity to absorb energy and deformation without collapsing in the post-ultimate stress region [36]. The ITS test results have been used in numerous studies [36][37][38][39][40] to calculate the toughness index (TI). TI is determined using Equation 2.…”
Section: Methodsmentioning
confidence: 99%
“…The Toughness Index (TI) is a parameter that describes the characteristics of toughness, which, as determined by the stress-strain curve, is the mixture's capacity to absorb energy and deformation without collapsing in the post-ultimate stress region [36]. The ITS test results have been used in numerous studies [36][37][38][39][40] to calculate the toughness index (TI). TI is determined using Equation 2.…”
Section: Methodsmentioning
confidence: 99%
“…The toughness index is a parameter that describes the behaviour of a solid material As depicted in Figure 4, the toughness index is calculated by dividing the area under compressive stress against time with details of the initial stress area up to 80% post-peak stress divided by the area from initial stress to peak stress, where in this study the y axis is compressive stress and the x axis is time. This calculation is based on previous studies (22,23).…”
Section: Toughness Indexmentioning
confidence: 99%
“…Additionally, the addition of plastic to asphalt bitumen helps the asphalt concrete mixture remain stable at high temperatures. Pasra et al (2015) [22] introduced a method called flexible pavement for road construction. Their study revealed that adding plastic waste to the mixture enhances the binding qualities, stability, density, and water resistance of the asphalt.…”
Section: Previous Empirical Research Studiesmentioning
confidence: 99%